Positive responses of flower visiting bees to landscape heterogeneity depend on functional connectivity levels - Boscolo, Danilo; Tokumoto, Paola Mandetta [UNESP]; Ferreira, Patrícia Alves; Ribeiro, John Wesley [UNESP]; Santos, Juliana Silveira dos [UNESP] (My University, 2017)
Landscape changes can lead to bee species loss, what impairs proper landscape level pollination processes, impacting both nature conservation and human welfare. Although landscape heterogeneity can rescue bee communities from collapsing, these insects seem sensitive to reduced functional connectivity, hindering pollen transfer among plants. Our objective was to verify which of these two factors, landscape heterogeneity or functional connectivity, can better explain variations of bee abundance and richness in a fragmented Atlantic Forest region. We sampled flower-visiting bees in 12 landscapes with varying heterogeneity and functional connectivity measured using a Functional Ecological Corridors framework. Both richness and abundance were affected by landscape factors, reaching its highest levels at intermediate levels of functional connectivity in highly heterogeneous landscapes, indicating the existence of strong regime shifts in the system. In low-forested landscapes, conservation actions for pollinating bees should focus on implementing diversified environments with high quality which are interspersed among each other and with native vegetation.
Keywords: Atlantic forest; Bee richness and abundance; Functional ecological corridors; Landscape effects; Pollination